Philosophical skills of education students at the preservice level - Acido, Maricris B. (2004)
This study is an investigation of education students' philosophical skills mainly conceptual analytic, linguistic, reasoning, and decision-making skills in resolving educational issues. It used the mixed-method design to answer problems or hypotheses raised in the study. Philosophical skills of the students were determined through content analysis of their philosophical papers on their analysis of an educational issue and through case studies. It was found that philosophical skills help students resolve educational problems and issues. Their acquisition of philosophical skills are affected by the high school they attended. They are weakest in linguistic skills and strongest in decision-making. Study habits, personality, motivation, disciplined and critical thinking and IQ are factors that determine students' philosophical skills.